2017
DOI: 10.1039/c7nj01886j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of boron carbon oxynitride films with tunable composition using methane, boric acid and ammonia

Abstract: This study highlights the synthesis and characterization of 2D BCNO films using the atmospheric pressure CVD technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(72 citation statements)
references
References 48 publications
4
68
0
Order By: Relevance
“…The D' peak is ascribed to the lattice vibration mode of the G peak at the surface of the carbon structure [31,32]. A similar D' peak has also been observed in boron carbon oxynitride films due to lattice distortions [33]. The existence of amorphous carbon in the nanomaterials was nonetheless further confirmed from the Raman spectra as shown in Figure 2 with the characteristic D, G and D' bands.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…The D' peak is ascribed to the lattice vibration mode of the G peak at the surface of the carbon structure [31,32]. A similar D' peak has also been observed in boron carbon oxynitride films due to lattice distortions [33]. The existence of amorphous carbon in the nanomaterials was nonetheless further confirmed from the Raman spectra as shown in Figure 2 with the characteristic D, G and D' bands.…”
Section: Resultssupporting
confidence: 63%
“…The D' peak is ascribed to the lattice vibration mode of the G peak at the surface of the carbon structure [31,32]. A similar D' peak has also been observed in boron carbon oxynitride films due to lattice distortions [33]. The high ID/IG ratio of the C-V2NO@800 °C recorded in Table 1 suggests that the presence of defects could result from the nitrogen incorporated in the carbon lattice and also the strong interaction between the metal oxynitride and the carbon.…”
Section: Resultssupporting
confidence: 54%
“…From Table 1 it can be observed that doping with boron and nitrogen atoms increased the defect density ratio (I D /I G ; 0.97) value in comparison with the moderate degree of graphitization of the CSs (i.e., I D /I G ≈ 0.91). This can be attributed to the presence of more defects associated with the incorporation of B and N atoms into the carbon structure [58,59]. A shift in the G bands of activated CSs and BN-CSs with respect to the non-activated CSs can be ascribed to structural defects [60] incorporated in the carbon matrix resulting in an increase in the I D /I G ratio values to 0.98 and 1.04, respectively (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…By the 500°C anneal the boron has become fully oxidised by forming B 2 O 3 . The corresponding component peaks in both the B 1s (193.3 eV) and O 1s (532.9eV) are now in the correct binding energy position for B 2 O 3 [9,10].…”
Section: A Characterisation Of Eld Co Filmsmentioning
confidence: 99%
“…Initial data from the as-received sample reveals the Si to Fig.4 The normalised N 1s and C 1s, show a deterioration in the signal to noise for the N 1s and the decomposition of the C 1s with increasing anneal temperature comprise of several different components which have been assigned to the bulk Si at 1839.1 eV, two Co silicide phases, one at 1839.5eV and the other at 1838.7eV, SiO 2 at 1843.7eV and sub oxide states on the HBE side of the bulk peak. The silicide phase on the HBE side has been attributed to CoSi [9,10] while the silicide on the LBE side has been attributed to Co 2 Si [11,12]. There is also a "pre-peak" observed on the LBE side.…”
Section: B the Si-co Interfacementioning
confidence: 99%